The Turkish Insurance Sector Performans Evaluation : DEA Malmquist Approach - (:unkn) unknown (INT BUSINESS INFORMATION MANAGEMENT ASSOC-IBIMA, 2014)
The survival of insurance companies, in the intense market competition, the most effective way to use different sources and with other companies in the sector by comparing their performance should be evaluated. Many inputs and outputs observed and observed that the input and output of a single total input and output can not be transformed in case the company's effectiveness is used to measure data envelopment analysis (DEA) in the efficiency analysis the most commonly used parameters of the methods is one. DEA models; input-oriented and output-oriented can be analyzed in two groups. Turkish Insurance sector, between 2005-2010, non-life insurance companies operating in considering variables related to the financial structure of the inputs and outputs of the model were created. DEA results, the company can not reach the vast majority of events in the direction of the border and establishing reference groups for these companies need in order to be effective potential improvement rates were obtained. On the other hand, the decision unit in a certain period of data needed to perform a cross-sectional analysis, DEA is a static analysis. In this study, as well as firms' total factor productivity changes and the reasons for these changes will be discussed with the Malmquist index of total productivity. you also; activities necessary for the creation of the index values calculated on the sector's future strategy will be informed about the creation.
Keywords: DEA; Malmquist total productivity; insurance; performance evaluation; ranking; OWNERSHIP STRUCTURE; EFFICIENCY; INDUSTRY